2019
DOI: 10.18632/aging.102074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcutaneous vagus nerve stimulation in individuals aged 55 years or above: potential benefits of daily stimulation

Abstract: Ageing is associated with attenuated autonomic function. Transcutaneous vagal nerve stimulation (tVNS) improved autonomic function in healthy young participants. We therefore investigated the effects of a single session of tVNS (studies 1 and 2) and tVNS administered daily for two weeks (study 3) in volunteers aged ≥ 55 years. tVNS was performed using modified surface electrodes on the tragus and connected to a transcutaneous electrical nerve stimulation (TENS) machine. Study 1: participants (n=14) received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 49 publications
12
100
0
4
Order By: Relevance
“…This indicates that taVNS is more efficient in older patients, a result that could be explained by lower starting levels of HRV in this group due to age-related decline in parasympathetic activity. The magnitude of taVNS-induced changes has been shown to be higher in individuals with lower starting HRV level (Bretherton et al, 2019). The taVNS significantly increased all HRV parameters: the mean R-R interval in 81%, Flexibility in 63%, Dynamics (RMSSD) in 69%, Tone in 68% of patients, and decreased the HRV age by 9 years.…”
Section: Hrv Tests and Results Of Test-tavnsmentioning
confidence: 95%
See 2 more Smart Citations
“…This indicates that taVNS is more efficient in older patients, a result that could be explained by lower starting levels of HRV in this group due to age-related decline in parasympathetic activity. The magnitude of taVNS-induced changes has been shown to be higher in individuals with lower starting HRV level (Bretherton et al, 2019). The taVNS significantly increased all HRV parameters: the mean R-R interval in 81%, Flexibility in 63%, Dynamics (RMSSD) in 69%, Tone in 68% of patients, and decreased the HRV age by 9 years.…”
Section: Hrv Tests and Results Of Test-tavnsmentioning
confidence: 95%
“…Because HRV is a biomonitor for ANS function, we also analyzed HRV changes before and immediately after acute test-taVNS. HRV as well as HR have been found to be useful in monitoring the effects of taVNS (Clancy et al, 2014;Antonino et al, 2017;De Couck et al, 2017;Ylikoski et al, 2017;Badran et al, 2018b;Bretherton et al, 2019). Clancy et al (2014) demonstrated that 15 min of taVNS administered to the tragus significantly increased HRV, at least partly through reduction of sympathetic nerve activity.…”
Section: Hrvmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are also investigating the potential health benefits of stimulating the vagus nerve through the outer ear (19). One study published in July found the self-administered stimulation boosted the quality of life, mood, and sleep compared with a sham treatment in older adults (20).…”
Section: Keeping Pacementioning
confidence: 99%
“…Most of the studies which evaluated the clinical efficacy of TENS were on young subjects. There was a limited number of studies, which have investigated the effect of aging on TENS application (Grant et al, 1999;Cheing, Hui-Chan & Chan, 2002;Ng, Leung & Poon, 2003;Bergeron-Vézina et al, 2015;Daguet et al, 2018;Bretherton et al, 2019). Bergeron-Vézina et al (2015) reported TENS as an effective nonpharmacological treatment option in young, but not in elderly subjects.…”
Section: Introductionmentioning
confidence: 99%